Analysis of a blast due to inadvertant mixing of ammonium sulfate and sodium hyplochlorite. Issue 1 (25th March 2015) - Norval, Graeme W.
Abstract : Ammonium sulfate and sodium hypochlorite are common industrial chemicals, often used together in water treatment. The consequences of mixing hypochlorite (chlorine) solution with ammonia solutions are well understood within the chlorine industry; detonable chloramines are produced. This knowledge is not well known in other industries; fortunately, few locations have both chemicals on site. These products were inadvertently mixed, resulting in an explosion, at a water treatment facility in Kitchener, Ontario on April 2, 2014. The chemistry of the incident is presented and discussed. Facilities that handle both chemicals, such as the water treatment industry need to have heightened sense of understanding of this particular reactive chemical hazard. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 92–95, 2016